The Interpersonal Meaning of the "Elephant" Report Text toward EFL Secondary Students’ Textbook - Bunga Agita Firnawati; Yogi Setia Samsi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
SFL analysis is very important to master in the grammatical field because it becomes the basis for analyzing and interpreting the meaning of a written or spoken text. This study analyzed a report text entitled "Elephant" using interpersonal meaning. The aim of this study is to identify the mood system contained in the report text, "Elephant," in an EFL secondary students’ textbook. This study employed a qualitative descriptive method using the research object, a report text titled "Elephant," and focused on analyzing the mood system that includes declarative mood, interrogative mood, and imperative mood. The findings of this study showed that the percentage of the mood system contained in the report text entitled "Elephant" is 100% declarative mood. This showed that the report text being analyzed contains information according to the function of the declarative mood, which is to describe information through a statement. It also revealed the writer-reader interaction, in which the writer, as the interlocutor, delivers information while the reader, as the recipient, receives it.